Explantation of High Submuscular Reservoirs: Safety and Practical Considerations. Issue 12 (16th November 2020) - Kavoussi, Mehraban; Bhanvadia, Raj R.; VanDyke, Maia E.; Baumgarten, Adam S.; Ortiz, Nicolas M.; Khouri, Roger K.; Ward, Ellen E.; Hudak, Steven J.; Morey, Allen F.
Abstract: Background: Over the past decade, high submuscular (HSM) placement of inflatable penile prosthesis (IPP) reservoirs has emerged as a viable alternative to space of Retzius (SOR) placement; however, data comparing the feasibility and complications of HSM vs SOR reservoir removal do not presently exist. Aim: To present a comparison of the safety, feasibility, and ease of removal of HSM vs SOR reservoirs in a tertiary care, university-based, high-volume prosthetic urology practice. Methods: Data were retrospectively collected on patients who underwent IPP reservoir removal between January 2011 and June 2020. Cases were separated into 2 cohorts based on reservoir location. Statistical analysis was performed using Fisher's exact and Chi-squared tests for categorical variables and Student's t -test for continuous variables. Timing from IPP insertion to explant was compared between the HSM and SOR groups using the Mann-Whitney U test. Outcomes: Time from IPP insertion to explant, operative time, intraoperative and postoperative complications, and need for a counter incision were compared between the HSM and SOR groups. Results: Between January 2011 and June 2020, 106 (73 HSM, 33 SOR) patients underwent IPP removal or replacement by a single surgeon at our institution. Average time from IPP insertion to removal was 43.6 months (24.2 HSM, 52.7 SOR, P = .07)—reservoir removal occurred at the time of device explant in 70 of 106 (66%) cases. More HSM reservoirs were explanted at the time of IPP removal compared with the SOR cohort (54 of 73, 74% HSM vs 16 of 33, 48.5% SOR, P = .01). Similar rates of complications were noted between the HSM and SOR groups (1.9% vs 6.3%, P = .35). There was no significant difference in need for counter incision between the 2 groups (24 [42%] HSM vs 4 [25%] SOR, P = .16) or in average operative times (76.5 ± 38.3 minutes HSM vs 68.1 ± 34.3 minutes SOR, P = .52). Clinical Implications: Our experience with explanting HSM reservoirs supports the safety and ease of their removal. Strengths and Limitations: Although the absolute cohort size is relatively low, this study reflects one of the largest single-institution experiences examining penile implant reservoir removal. In addition, reservoir location was not randomized but was instead determined by which patients presented with complications necessitating reservoir removal during the study period. Conclusions: HSM reservoir removal has comparable perioperative complication rates and operative times when compared with SOR reservoir removal.